Lfo-miR164b and LfNAC1 as autumn leaf senescence regulators in Formosan sweet gum (Liquidambar formosana Hance) - Wen, Chi-Hsiang; Hong, Syuan-Fei; Hu, Sin-Fen; Lin, Shih-Shun; Chu, Fang-Hua (Plant science (Limerick), 2020)
•Lfo-miR164b module was identified as a putative autumn leaf senescence regulator in Formosan sweet gum.•Lfo-miR164b promotes the degradation of the leaf senescence transcription factor LfNAC1.•LfNAC1 promotes chlorophyll degradation and the transcription of the enzyme encoding gene LfSGR. In this study, a microRNA microarray was used to investigate the microRNA profiles from young green leaves, and senescent red leaves and yellow leaves of Formosan sweet gum (Liquidambar formosana Hance). The conserved microRNA miR164 was highly expressed in green leaves compared to senescent leaves. The pri-microRNA of miR164 was identified and named lfo-miR164b based on its secondary structure. In Agrobacterium-mediated transient expression experiment, lfo-miR164b was confirmed to regulate the leaf senescence-associated gene LfNAC1 and LfNAC100. Transient overexpression of LfNAC1 induced the expression of leaf senescence genes in Nicotiana benthamiana. In addition, LfNAC1 activated the expression of proLfSGR::YFP, suggesting the regulatory role of LfNAC1 in leaf senescence. In summary, miR164 inhibits the expression of LfNAC1 in spring and summer, later on LfNAC1 actives leaf senescence-associated genes to cause leaf senescence following a gradual decline of miR164 as the seasons change. The “miR164-NAC” regulatory mechanism was confirmed in Formosan sweet gum autumn leaf senescence.